2002
DOI: 10.1080/078538902321117760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormone suppression therapy on adverse clinical outcomes in thyroid cancer

Abstract: THST appears justified in ThyrCa patients following initial therapy. As most primary studies were imperfect, future research will better define the effect of THST upon ThyrCa clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
3
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(132 citation statements)
references
References 45 publications
0
118
3
9
Order By: Relevance
“…Suppression of TSH, using supraphysiologic doses of LT 4 , is used commonly to treat patients with thyroid cancer in an effort to decrease the risk of recurrence (73,168 …”
Section: What Is the Role Of Tsh Suppression Therapy?mentioning
confidence: 99%
“…Suppression of TSH, using supraphysiologic doses of LT 4 , is used commonly to treat patients with thyroid cancer in an effort to decrease the risk of recurrence (73,168 …”
Section: What Is the Role Of Tsh Suppression Therapy?mentioning
confidence: 99%
“…There is a report stating that postoperative TSH suppression therapy can reduce the recurrence rate [13], but there is no substantial evidence to support this. Once the administration of L-thyroxine is started, for the purpose of suppressing TSH, the medication must, theoretically, be continued for the remainder of the patient's life.…”
Section: Treatment Modalities For Large Papillary Thyroid Carcinomas mentioning
confidence: 99%
“…A tendency for a greater degree of TSH suppression to be associated with less disease progression was seen in a cohort of high-risk patients (10), although the difference did not reach significance. A meta-analysis that quantified adverse clinical outcomes from ten studies of patients on TSH suppression also suggested a benefit of this approach (11). However, some authors conclude that the benefit of TSH suppression is limited to patients with persistent or recurrent disease (12).…”
Section: Introductionmentioning
confidence: 99%